Drug transporters - Fromm, Martin F.; Kim, Richard B.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
It is increasingly recognized that various transporter proteins are expressed throughout the body and determine absorption, tissue distribution, biliary and renal elimination of endogenous compounds and drugs and drug effects. This book will give an overview on the transporter families which are most important for drug therapy. Most chapters will focus on one transporter family highlighting tissue expression, substrates, inhibitors, knock-out mouse models and clinical studies.
From the contents -- Preface -- Organic anion transporting polypeptides (OATPs); In vitro and in vivo evidence for the importance of organic anion transporters (OATs) in drug therapy; In vitro and in vivo evidence for the importance of organic cation transporters (OCTs, MATEs) in drug therapy; Intestinal bile salt transporters (ASBT and OST alpha/beta); hepatic bile salt transporters (NTCP and BSEP); Importance of P-glycoprotein for drug-drug interactions; Importance of the multidrug resistance protein (MRP) family for pathophysiology and drug therapy; Importance of breast cancer resistance protein transporters (BCRP); Molecular mechanisms of drug transporters regulation; In vivo probes of drug transport.
Electronic reproduction.
Keywords: Biological transport -- Physiology; Membrane transport proteins -- Physiology; Pharmacokinetics; Drug carriers (Pharmacy); Carrier proteins; Drugs -- Physiological transport; Pharmacology; Electronic books